Semi-Rigid Pneumatic Ureteroscopicremoval of Ureteric Stone; Seven Years Experience At Nepalgunj Medical College - Shrestha, Naresh Man (Journal of Nepalgunj Medical College, 2017)
Background: The present study aimed to report the outcomes of ureteroscopy (URS) treatment of ureteric stone with semi-rigid pneumatic ureteroscopic lithotripsy.Method: This was a prospective observational study of the patients who underwent ureteroscopic removal of ureteric stone in the department of surgery, urology unit, Nepalgunj Medical College from January 2009 to July 2015. All patients underwent urereroscopic removal of stones located at different levels of the ureter using semi-rigid 8/9.8 Fr ureteroscope.Result: 1251 patients with ureteric stones who underwent URS during the study period. Out of 1251 patients, in 1211 (96.80%) stone was removed in first setting, 10(0.79%) patients needed second setting of URS to remove stones. The overall failure rate was 1.59%. The common complications of URS observed were perforations of the ureteric wall (20%), retropulsion of ureteric stone into kidney (35%) and urosepsis (45%) which necessitated ureterolithotomy, Extra Corporeal Shock Wave Lithotripsy (ESWL) and antibiotic therapy, respectively. Two (0.15%) patients died and the cause was urosepsis with multiorgan failure in both.Conclusion: Most of the ureteric stone can be removed in a single setting of URS. However, some complications such as, ureteral trauma, difficulty in fragmentation of a stone, retropulsion of stone into the kidney and a fatal urosepsismay occur in few cases. Therefore, URS is a useful modality to remove the ureteric stones despite its few complications.JNGMC Vol. 13 No. 2 December 2015, page: 10-12